Tipos de Violencia de Pareja en Estudiantes De 17 A 24 Años De Una Universidad Privada De Bogotá. - Mateus Núñez, Carlos Andrés (Universidad Antonio Nariño, 2024)
This research is a quantitative, transversal and descriptive study and had purpose to explore if does exist any type of violence in dating relationships with students between 17 and 24 years of a private university from Bogotá. The type of sample is incidental and therefore has been applied a descriptive checklist instrument of experiences of abuse in the couple about 79 questions to 100 students created by Rey Anacona. 91% informed to have been object, at least once, of some abusive behavior. Not statistical differences by sex, career, age, socioeconomic level and employment information were found in this research. The more frequent maltreatment type was the psychological, continued by emotional, physical, economical and sexual